2017
DOI: 10.1038/s41598-017-09129-w
|View full text |Cite
|
Sign up to set email alerts
|

A clue to unprecedented strategy to HIV eradication: “Lock-in and apoptosis”

Abstract: Despite the development of antiretroviral therapy against HIV, eradication of the virus from the body, as a means to a cure, remains in progress. A “kick and kill” strategy proposes “kick” of the latent HIV to an active HIV to eventually be “killed”. Latency-reverting agents that can perform the “kick” function are under development and have shown promise. Management of the infected cells not to produce virions after the “kick” step is important to this strategy. Here we show that a newly synthesized compound,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
1
43
0
1
Order By: Relevance
“…The cells were analyzed by a fluorescence microscope Biorevo Fluorescence BZ‐9000 (Keyence). The number of apoptotic cells (Annexin V), late apoptotic or necrotic cells (Annexin V and Ethidium homodimer III), and necrotic cells (Ethidium homodimer III) were counted as previously described (Tateishi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were analyzed by a fluorescence microscope Biorevo Fluorescence BZ‐9000 (Keyence). The number of apoptotic cells (Annexin V), late apoptotic or necrotic cells (Annexin V and Ethidium homodimer III), and necrotic cells (Ethidium homodimer III) were counted as previously described (Tateishi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…To this end, TLR agonists offer promise due to their ability to induce a broad anti-viral response, simultaneously activating virus production and priming immune clearance of HIV-1 infected cells (Borducchi et al, 2016;Tsai et al, 2017;Lim et al, 2018;Macedo et al, 2018). To circumvent the need for CTL mediated cell clearance altogether, an alternative approach is to block the release of virions and induce apoptosis of the infected cell (Tateishi et al, 2017). In this method, a novel compound is used to inhibit HIV-1 Pr55 Gag , blocking virus budding and leading to a build-up of viral products and subsequent apoptosis of the infected cell (Figure 1; Tateishi et al, 2017).…”
Section: Shock and Killmentioning
confidence: 99%
“…To circumvent the need for CTL mediated cell clearance altogether, an alternative approach is to block the release of virions and induce apoptosis of the infected cell (Tateishi et al, 2017). In this method, a novel compound is used to inhibit HIV-1 Pr55 Gag , blocking virus budding and leading to a build-up of viral products and subsequent apoptosis of the infected cell (Figure 1; Tateishi et al, 2017).…”
Section: Shock and Killmentioning
confidence: 99%
“…any of currently approved antiretroviral drugs [11][12][13]. Based on the structural information of the MA domain and PI(4,5)P2, we recently developed a non-natural derivative of PI(4,5)P2, named L-HIPPO, which binds to the MA domain in order to eradicate HIV [14,15]. Recent progress identifying cellular interactions of HIV-1 Gag has revealed that the MA domain of the Gag is capable of binding to inositol hexaphosphate (IP6) [14,16] ( Figure 2B & C).…”
Section: Introductionmentioning
confidence: 99%